2018
DOI: 10.32474/mams.2018.01.000107
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Citrus Aurantifolia Leaves Extracts Against Some Enteric Bacteria of Public Health Importance

Abstract: The study was conducted to determine the phytochemical composition and antibacterial activity of Citrus aurantifolia leaves extracts against clinical isolates of some enteric bacteria of public health importance. The result of phytochemical screening of the leaves extracts shows the presence of alkaloid, glycoside, saponin, tannin, flavonoid, steroids, terpenoid and phenol. The result of antibacterial efficacy of the extracts against the isolates indicated that the extracts were active against the isolates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
1
1
0
1
Order By: Relevance
“…The result of the antibacterial activity of C. aurantifolia leaves extracts in the present study was in conformity with studies that reported its antibacterial potentials (25,26). The molecular report of the target genes in the respective bacteria was confirmatory because they conform to the expected band size as reported by Woodford et al, (27), Zhang et al, (28) Maheux et al, (29) and Einas et al, (30).…”
Section: Discussionsupporting
confidence: 93%
“…The result of the antibacterial activity of C. aurantifolia leaves extracts in the present study was in conformity with studies that reported its antibacterial potentials (25,26). The molecular report of the target genes in the respective bacteria was confirmatory because they conform to the expected band size as reported by Woodford et al, (27), Zhang et al, (28) Maheux et al, (29) and Einas et al, (30).…”
Section: Discussionsupporting
confidence: 93%
“…The ethanolic extract of C. aurantifolia leaves exhibited higher antibacterial activity than the aqueous one against Klebsiella bacteria and Escherichia coli, though the isolates showed distinct susceptibility to one another [89]. It is possible that the higher activity of the ethanolic extract can be attributed to the better solubility of the secondary metabolites than the aqueous ones, thus leading to better efficacy.…”
Section: Antibacterialmentioning
confidence: 96%
“…Ekstrak air daun jeruk nipis (Citrus aurantifolia) dapat menghambat pertumbuhan bakteri Salmonella typhi dan Escherchia coli dengan berbagai konsentrasi. Konsentrasi yang paling baik dalam menghambat pertumbuhan bakteri adalah 25% dengan nilai hambat 11,25 mm dan 12,33 mm (Zage et al, 2018).…”
unclassified